ANALISIS FAKTOR PENDORONG SISWA DI BAWAH UMUR MENGENDARAI KENDARAAN RODA DUA DITINJAU DARI CIVIC KNOWLEDGE PADA SISWA KELAS X SMA NEGERI 5 KOTA JAMBI - Aulia, Nurul Quraini; Anderson, Irzal; Sariani, Dona (UNTIRTA CIVIC EDUCATION JOURNAL, 2025)
The phenomenon of underage students riding two-wheeled vehicles is increasingly common, including at SMA Negeri 5 Jambi City. This research aims to analyze the factors driving this behavior by reviewing the civic knowledge aspect. This research uses a descriptive qualitative method, with data collection techniques through interviews and questionnaires with class Even though most students know that underage driving is against the rules, they still do it out of necessity and lack of supervision. The civic knowledge that students have is not enough to encourage compliance with traffic rules. Therefore, a more comprehensive approach is needed through strengthening the role of the family, enforcing discipline in schools, and increasing legal awareness in the community in order to minimize underage driving violations.   Keywords: underage students, two-wheeled vehicles, civic knowledge, driving factors, traffic safety.